2002
DOI: 10.1139/w01-136
|View full text |Cite
|
Sign up to set email alerts
|

Early interactions ofEntamoeba histolyticatrophozoites with parenchymal and inflammatory cells in the hamster liver: an immunocytochemical study

Abstract: We studied the early in situ interactions of live and fixed Entamoeba histolytica trophozoites with hamster hepatic parenchymal and inflammatory cells using immunoperoxidase and immunoelectronmicroscopy. Close contact between trophozoites and endothelial cells and the diffusion of amoebic molecules from trophozoites towards nearby endothelial cells and distant hepatocytes were observed. The inflammatory cells around the amoebae and the remnants of parenchymal cells and hepatocytes located close to the lesion h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Then, they were washed in PBS for 5 min and incubated in 20% fetal bovine serum (Hyclone) in PBS for 30 min and then washed three times with 0.025% PBS-tween for 10 min. The slides of infected and uninfected tissue were incubated with the primary antibody for 12 h using the following dilutions: 1:500 rabbit anti-E. histolytica immune serum raised in our laboratory (Ventura-Juárez et al 2002) and 1:100 mouse anti-human CD59 monoclonal antibody (Chemicon international CBL467 suitable for immunohistochemistry). All slides were washed with 0.025% PBS-tween for 10 min.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Then, they were washed in PBS for 5 min and incubated in 20% fetal bovine serum (Hyclone) in PBS for 30 min and then washed three times with 0.025% PBS-tween for 10 min. The slides of infected and uninfected tissue were incubated with the primary antibody for 12 h using the following dilutions: 1:500 rabbit anti-E. histolytica immune serum raised in our laboratory (Ventura-Juárez et al 2002) and 1:100 mouse anti-human CD59 monoclonal antibody (Chemicon international CBL467 suitable for immunohistochemistry). All slides were washed with 0.025% PBS-tween for 10 min.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Tsutsumi et al [24] and Ventura-Juarez et al [53] showed that E. histolytica trophozoites are capable of inducing an important inflammatory response via polymorphonuclear and mononuclear leukocytes in hamsters. Pacheco-Yepez et al [54] demonstrated, through immunohistochemistry and PCR techniques, that the immune response to E. histolytica invasion includes a gradual increase in TNF-α, IFN-γ, IL-8, and IL-1β during the early stages (the first 3 h) of ALA development.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments show that amebas secrete proteases into the culture medium (Leippe et al 1995;Reed and Gigli 1990;Serrano et al 1996) and it is suggested that such proteases are responsible, at least in part, for the extensive tissue destruction characteristic of the disease. Using a polyclonal antibody raised against whole amebic extracts, Ventura-Jua´rez et al (1997) stained immunohistochemically early experimental amebic lesions and showed that not only were trophozoites positive but also that there was diffusion of positive material in the vicinity of amebas. Using a polyclonal antibody antiEhCP1, Stanley et al (1995) were able to stain amebic trophozoites in acute experimental liver abscesses produced in SCID mice; and they claim to have detected positive staining in the tissues near the parasites.…”
Section: Discussionmentioning
confidence: 99%